Faktor Risiko Kejadian Scabies pada Santri Pondok Pesantren - Sukmawati, Sukmawati; Ahmad, Haeranah; Islam, Fahrul; Akbar, Fajar (Universitas Kristen Maranatha, 2025)
Scabies remains a significant public health issue in Indonesia, with prevalence rates of 5.6-12.9%, ranking as the third most common skin disease. Poor personal hygiene and limited knowledge of prevention are key contributing factors. This study aimed to analyze the relationship between room occupancy density and personal hygiene with the incidence of scabies among students at Mts Raudhatut Tholibin Tohri Islamic Boarding School located in Mamuju Subdistrict, Mamuju Regency, Indonesia. An analytic observational study using a cross-sectional design was conducted with 109 respondents selected through purposive sampling. Data were collected via field observations and structured interviews, then analyzed using chi-square tests. Results showed significant associations between scabies and skin cleanliness (p=0.001), nail hygiene (p=0.001), clothing cleanliness (p=0.001), mattress hygiene (p=0.001), pillow cleanliness (p=0.001), bedsheet hygiene (p=0.001), and towel cleanliness (p=0.001). No significant association was found between scabies and prayer equipment cleanliness (p=0.328). All dormitories exceeded recommended occupancy standards. In conclusion, personal hygiene factors (particularly skin, clothing, and bedding cleanliness) significantly correlate with scabies incidence. In conclusion, reducing scabies prevalence in boarding schools requires targeted hygiene interventions, better room occupancy management, strengthened health education, and active collaboration with local health services to ensure long-term prevention.